Nursing care of a patient with ischemic stroke complicated with pulmonary infection by aerosol inhalation of traditional Chinese medicine (中药雾化吸入在1例缺血性脑卒中并发肺部感染患者护理中的应用) - GAO Ya (高雅); LIU Guiying (刘桂英); TANG Ling (唐玲); ZHOU Jie (周洁); ZHANG Yanyan (张艳艳) (中西医结合护理)
This paper reviewed the nursing experience of an elderly patient with ischemic cerebrovascular disease complicated with pulmonary infection. On the basis of routine treatment and nursing intervention of pulmonary infection, the traditional Chinese medicine aerosol inhalation nursing was given. The implementation of atomized inhalation of traditional Chinese medicine can obviously reduce the viscosity of sputum of patients, and reduce the number of times of daily sputum aspiration. (本文回顾1例缺血性脑卒中并发肺部感染老年患者的护理经验。在常规肺部感染治疗、护理干预的基础上, 给予中药雾化吸入。中药雾化吸入能够有效降低患者痰液的黏稠度, 减少患者每日吸痰次数。)